Common Variants in the Periostin Gene Influence Development of Atherosclerosis in Young Persons - Hixson, James E.; Shimmin, Lawrence C.; Montasser, May E.; Kim, Do-Kyun; Zhong, Yu; Ibarguen, Heladio; Follis, Jack; Malcom, Gray; Strong, Jack; Howard, Tim; Langefeld, Carl; Liu, Yongmei; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2011)
OBJECTIVE—We investigated the influence of genetic variants (rare and common) in the gene encoding periostin (POSTN) on atherosclerosis as measured in arterial specimens from the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) study. METHODS AND RESULTS—A comprehensive survey of common POSTN variants (87 single-nucleotide polymorphisms [SNPs]) in PDAY subjects (n=2527) identified numerous SNPs associated with raised lesions in abdominal aorta and with fatty streaks in thoracic aorta. These SNPs belonged to a small number of correlation bins that spanned the entire locus. To examine effects of rare variants, we resequenced POSTN functional regions in PDAY cases with raised lesions (n=291) and controls with no raised lesions (n=294). However, we found no significant associations with case-control status for carriers of POSTN rare variants using the weighted-sum method for rare variant analysis. CONCLUSION—We identified common variants in POSTN that are associated with arterial lesions in young persons from the PDAY study. This finding strongly supports a role for periostin in atherogenesis, as suggested by recent proteomics analysis that found abundant expression of periostin in atherosclerotic lesions. Genetic variation may influence atherosclerosis via periostinʼs known involvement in multiple relevant pathways, including angiogenesis, vascular remodeling, and stimulation of migration and differentiation of vascular smooth muscle cells.